Semantic Deviation in Classical Poem Interpretation: A Perspective from Beginning Training Course Students in TEFL - Andriadi Andriadi (AL LUGHAH, 2019)
Manipulation of language used in poems to state poet’s idea is basically aimed to give aesthetic value, help the readers to easily understand, and give complete image of the text meaning. However, in a real application in the classroom, the language style in poems causes language deviation and covers the poet’s idea. Readers should read the poems explisitly in deep interpretation to get the meaning. Therefore, this study describes an eight-week (135 minutes a week) poem stylistics of semantic deviation analysis for a half –semester beginning training course (poetry class) for the use of literature in an EFL context. The research was conducted at the fourth semester students of English Program of IAIN Bengkulu in academic year 2017/2018 that consisted of 31 students. This descriptive analysis aimed to describe students’ exploration of semantic deviation in classical poem interpretation. The result showed that Wordsworth’s The Solitary Reaper used various kinds of semantic deviation in forms of language stylistics of figurative languages, namely: (1) semantic Bizarreness of expression that consisted of oxymoron and paradox; (2) transference of meaning that consisted of synecdoche, metonymy and metaphor; (3) Misrepresent the truth that consisted of hyperbole and irony. In a real analysis of the poem, the students were excellent in identyfying the kinds of language deviations. Then, they were very good at understanding the poem literally. However, they had problems in interpreting the poet’s real meaning through semantic deviation used in the poem because they needed more experience about lingistic, social and historical background knowledge of classical England, and biography of the poet.